Onde estão os livros? uma história da Biblioteca Pública de Brejinho-PE (1964-2005) - Costa Filho, Abrahão Francisco da (2021)
The referred undergraduate thesis aims to investigate and analyze the process through which books and printed materials reach cities in the interior of Brazil, specifically in Brejinho, city which the research is realized in, covering the period between 1964-2005. We seek to understand the circumstances in which the Municipal Public Library of this town was established and its development over the years, seeing the public policies emerging from the sphere of federal government and its arrival in the small town; as well as practices developed by municipal management for foundation and maintenance of reading spaces. For this, it is necessary to situate the town in this context, highlighting the main points of its history; it also treated of the question of access to books and the reading in the social sphere, and also the encountered challenges for a formation of a reader society. Thus, the works by authors such as: Chartier (1999, 2003), Abreu (1999, 2010), Milanesi (1986, 1998, 2002), Araújo (2002), Almeida Júnior (2016), Casson (2018), Ferreira (2016), Barbier (2018), Goulemot (2011), Higounet (2003), Babosa (2007), Febvre and Martin (2017), Gomes (2005), Motta (2009), Sirinelli (2003), among others, gave us support for reasoning of work. Along this path, several sources were identified in collection among which we can highlight: the files of Town Hall and of the Chamber of the Councilors, files of Library Manoel Nunes Ferreira, and of the schools São Sebastião and José Severino de Araújo and the Parish of São Pedro‘s Book of Tombo in Itapetim, Parish of São José in São José do Egito and Parish of São Sebastião in Brejinho. Some of the printed are available on the National Library website and were also important for research such as: Jornal do Recife, Diário de Pernambuco, Última Hora, and A Província, as well as data from IBGE and other federal and state agencies when they were needed. In this perspective, it is intended to understand the path followed through printed material and how it arrived in the interior of the state of Pernambuco enabling modifications or not in the current structures, highlighting the importance of reading and the barriers that are constantly imposed for its realization. Therefore, this dissertation is inserted in the line of research History and Regionalities within the History and Historical Culture concentration area of the Graduate Program degree in History from the Federal University of Paraíba - UFPB.